Pengaruh keluarga besar terhadap per kembangan kecenderungan neurotik pada remaja - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRAK A causal comparative study has been conducted to know the effect of large family on the development of adolescence neurotic tendency. The study subjects are of Senior High School students in Sleman Regency. The neurotic tendency was assessed by administering the Eysenck Inventory Questionaire on the subject. The result showed that there in significant difference in the neurotic tendency between two categories of family size as well as gender.